Malaysian Spending Patterns Prior to Goods and Services Tax (GST) Implementation - Kamaruddin, Rohana; Mustapha, Nurol Ain (International Journal of Supply Chain Management, 2017)
Do Malaysian consumers have fair knowledge about GST, is there a strong association between gender and spending patterns, and do demographic factors strongly influence level of spending among Malaysian consumers were issues addressed in this study. 730 respondents were selected and interviewed using a structured questionnaire a week after the implementation of GST. Study findings showed that Malaysian consumers do have fair knowledge about GST and will still give priority to accommodation, followed by groceries, food, transportation, clothing, communications/internet and entertainment. There were no strong association between gender and spending patterns. However, Age and work sectors appeared to significantly influence the pattern. Based on our Logistics Regression Analysis, we predict that people would not spend after GST is implemented, thus, the implementation of GST will not get its desired results. We proposed that the Ministry of Finance, among other measures, should consider adding more products/ services in zero-rated basket.